What women think about menopause: An Italian survey. (May 2021) - Vaccaro, Concetta Maria; Capozzi, Anna; Ettore, Giuseppe; Bernorio, Roberto; Cagnacci, Angelo; Gambacciani, Marco; Coletta, Vittoria; Maffei, Silvia; Nappi, Rossella Elena; Scambia, Giovanni; Viora, Elsa; Lello, Stefano
Highlights: Menopause is a critical period for women's health. Menopause was considered a physiological condition by our sample of Italian women. Italian women experiencing menopausal symptoms rely on hormonal and non-hormonal treatments in similar proportions. Satisfaction about Italian National Health System and medical experience on menopause is moderate. Abstract: Introduction: Menopause is a critical period for most women who experience associated symptoms while they are still socially and individually active. Objectives: The objective of this study is to report how Italian women perceive and approach menopause. Materials and methods: A survey of 1028 Italian women aged 45–65 years was conducted by the Italian Center for Studies of Social Investments (CENSIS) through anonymous interviews using two methods: CATI (Computer Assisted Telephone Interviewing) and CAWI (Computer Assisted Web Interviewing). Principal outcome measures: Principal outcome measures were women's perceptions and experiences of menopause and its treatments. Results: The global consciousness and understanding of menopause was common (82.8 %) among Italian women and it was usually considered a physiological condition (77 %). Overall, 74.6 % of the sample were postmenopausal. Hot flushes were reported to be the most frequent (37.9 %) and bothersome symptoms (43.1 %) while 12.9 % of the women were asymptomatic. As for menopausal therapies, 24.5 % were on treatment; herbal medications were the most common remedy (63.3 %) whereas 7.6 % of the women took hormone replacement therapy (HRT). About half of the sample (50.4 %) had not sought help from the Italian National Health System (INHS). Medical expertise in the field of menopause was thought to be moderately satisfactory by 54.5 % of the sample. Conclusions: Italian women consider menopause a physiological condition. Most postmenopausal women had experienced symptoms but relied on non-hormonal treatments. The median women's satisfaction with the role of the INHS and medical competence suggests the need to improve current knowledge and awareness concerning menopause.